1983
DOI: 10.1093/jn/113.2.328
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Manganese Deficiency on Cholesterol and Lipid Metabolism in the Wistar Rat and in the Genetically Hypercholesterolemic RICO Rat

Abstract: Two experiments were conducted to determine the effect of dietary manganese on cholesterol and lipid metabolism in the Wistar rat and the genetically hypercholesterolemic RICO rat. Weanling animals were placed on a manganese-deficient (0.12 microgram/g) and a supplemented diet (100.12 micrograms/g). Mean body weights, hepatic fatty acid synthesis and liver manganese concentration significantly decreased in the deficient group of Wistar rats. Plasma cholesterol, VLDL (very low density lipoprotein) and HDL (high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Our results are in accordance with the findings of Klimis-Tavantzis et al [31] who reported that plasma cholesterol and liver lipid content are not significantly affected by Mn supplementation. Also, Hellerstein et al [32] reported that high dietary Mg appears to be anti-sudanophilic only when the serum cholesterol level was ele vated to 400 mg/dl or above.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are in accordance with the findings of Klimis-Tavantzis et al [31] who reported that plasma cholesterol and liver lipid content are not significantly affected by Mn supplementation. Also, Hellerstein et al [32] reported that high dietary Mg appears to be anti-sudanophilic only when the serum cholesterol level was ele vated to 400 mg/dl or above.…”
Section: Discussionsupporting
confidence: 94%
“…Mice fed an Mn-deficient diet showed no significant al terations either in the plasma cholesterol level or in liver lipid content. Our results are in accordance with those of Klimis-Tavantzis et al [31 ] who found that liver lipid con tent and plasma cholesterol level were not affected by either the type of RICO rats or dietary treatment. Coupled deficiency was the only dietary treatment that showed a greater diversity when compared to the con trol group.…”
Section: Discussionsupporting
confidence: 93%
“…Kawano et al [12] reported that animal fed with Mn-deficient diet (1 ppm Mn) had depressed blood HDL protein, HDL-cholesterol, and apo E levels. Klimis-Tavantzis et al [13] observed the reducing effect of Mn deficiency upon plasma LDL-cholesterol levels in Wistar rats and genetically hypercholesterolemic RICO rats. It was suggested that Mn may be essential to the lipoprotein structure [29] due to its high affinity for complexing with the polar heads of phospholipids, thereby stabilizing the lipoprotein particle [30].…”
Section: Discussionmentioning
confidence: 99%
“…Kawano et al [12] reported that animals that were fed small amounts of Mn had depressed blood high-density lipoprotein (HDL) and HDL-cholesterol levels. Klimis-Tavantzis et al [13] also observed the effect of Mn deficiency on reducing plasma high-density lipoprotein (LDL) cholesterol levels in Wistar rats and genetically hypercholesterolemic RICO rats. These studies suggested possible effects of Mn intake on blood lipid metabolism, but most of the studies observed the change of lipid metabolism in condition of Mn deficiency and not in cases of Mn supplementation.…”
mentioning
confidence: 98%
“…The epidemiological studies showed that trace elements Fe, Zn and Cu were related to the incidence of coronary artery disease, and the mechanism is related to vascular cell dysfunction and inflammatory reaction [13,14,15]. It was reported that the deficiency of Mg causes the inhibition of glucose tolerance, carbohydrate and lipid metabolism, and degradation of serum high density lipoprotein [16,17].…”
Section: Introductionmentioning
confidence: 99%